ANALYSIS OF WATER DEMAND AND AVAILABILITY IN WAE MESE I WATER TREATMENT PLANT TO NUMBER OF CUSTOMERS IN 2030 (CASE STUDY: PERUMDA AIR MINUM WAE MBELILING) - Dasor, Apolinaris; Saves, Faradlillah (Jurnal Teknik Sipil, 2023)
Start with bathing, washing, and cooking, and then move from these three activities to the parts of the human body, one of which is water. The need for clean water is increasing along with population growth. In this study, an analysis of the need for and availability of clean water was carried out in the service area of the Wae Mese I Water Treatment Plant (WTP), which covers seven urban villages in the Kecamatan Komodo. Projected water demand is based on population growth from 2021 to 2030. Projected water availability is based on the production capacity of WTP Wae Mese I from 2021 to 2030. Based on projected water demand and availability, water balance and WTP production capacity were analyzed in 2030.Based on the analysis of the results, the population in 2030 will reach 45715 people, and the total water demand in 2030 will be 62.06 liters/second. Meanwhile, the capacity of WTP Wae Mese I 40 liters/second has decreased to 33.81 liters/second in 2030. This results in a water deficit of 28.25 liters/second.